The The Law on Marriage for Pregnant Women Due to Adultery in the Socio-Cultural Perspective of Society - Anie Rohaeni; Mohd Imraan (The International Journal of Law Review and State Administration, 2023)
This research wants to explore the law, factors and causes, implications, public perception, and efforts to overcome pregnancy in marriage due to adultery. This research method is a qualitative descriptive approach. Data collection techniques through a. Observation at the research location. In-depth interviews with informants. Documentation of existing data such as meeting notes, books, and archives related to research. The conclusion is that the impact of cases of pregnant marriages due to adultery which occur repeatedly has shown that there is a form of announcement that reflects a shift in the socio-cultural perception of society regarding the issue of marriages of pregnant women due to adultery. This reality is contradictory in the context of social law. Efforts to address the problem of pregnant marriages have been carried out by existing social institutions that do not represent comprehensive and systematic efforts. Therefore, reconstruct the societal paradigm regarding the issue of marriage, and pregnancy due to adultery. To resolve problems that must receive attention from various parties.